Socio-Economic Status of Pomegranate Growers under National Horticulture Mission (NHM) in Solapur District and Constraints Faced by Them - T. S. Waghmode , M. C. Ahire; S. H. Ban (Indian Journal of Extension Education, 2013)
The present study was conducted to study socio-economic status of pomegranate growers in Sangola and Malshiras tehsils of Solapur district. It observed that nearly two third (60.83%) of pomegranate growers belonged to middle age between 33 to 56 years. More than two third (71.66 %) of pomegranate growers had used medium sources of information. Maximum number of pomegranate growers (77.50%) had medium level of scientific orientation. A majority of pomegranate growers (63.33 %) were in the medium level of planning orientation category. Nearly two third (65.83%) of the pomegranate growers belonged to medium risk orientation. The study pointed out that 47.50 per cent of the respondents possessed favourable attitude towards NHM. A majority of respondents (66.67%) had medium area under pomegranate cultivation (1 to 4 ha.). More than one-third (37.50%) of pomegranate growers had medium land holding between 4.01 to 10 ha. A majority of pomegranate growers (91.66 %) and (87.50%) had used radio and TV as source of information respectively. Very high majority (74.16%) of the pomegranate growers obtained information from friends/relatives, while nearly two third (62.50%) of pomegranate growers had always received information through Radio, followed by Newspaper (56.66 %) and Television (50.83 %). It was observed that under supply constraints, majority (100.00 %) of pomegranate growers had faced the constraint of lack of availability of disease resistant varieties.